Solvent‐Dependent Synthesis of Porous Anionic Uranyl–Organic Frameworks Featuring a Highly Symmetrical (3, 4)‐Connected ctn or bor Topology for Selective Dye Adsorption. Issue 3 (29th November 2016) - Hu, Kong‐Qiu; Jiang, Xiang; Wang, Cong‐Zhi; Mei, Lei; Xie, Zhen‐Ni; Tao, Wu‐Qing; Zhang, Xiao‐Lin; Chai, Zhi‐Fang; Shi, Wei‐Qun
Abstract: Two highly symmetrical (3, 4)‐connected uranyl–organic frameworks (UOFs) were synthesized by a judicious combination of D 3 h ‐symmetrical triangular [UO2 (COO)3 ] − and Td symmetrical tetrahedral tetrakis(4‐carboxyphenyl)methane (H4 MTB). These two as‐synthesized UOFs possess similar structural units and coordination modes but totally different topological structures, namely ctn net and bor net. Solvent‐induced interpenetration and a morphology change are observed. The two compounds exhibit crystal transformation via a dissolution–crystallization process. Adsorption experiments in CH3 OH solution indicate that both of them can selectively remove positively charged dyes over negatively charged and neutral dyes. Moreover, the electronic structural and bonding properties of the two compounds were systematically explored by density functional theory (DFT) calculations. Abstract : Two uranyl–organic frameworks (UOFs) based on the MTB 4− ligand, C( p ‐C6 H4 COO − )4, were synthesized by altering solvents. They possess similar structure units and coordination modes but totally different 3D structures, featuring ctn ‐type and bor ‐type topology.